Affirmative action and social stereotypes: Deconstructing the myth of minority inferiority - Souza, Eloisio Moulin de (Education Policy Analysis Archives, 2019)
Affirmative action aimed at promoting access for groups considered minority to universities are important for combating structural inequalities and promoting social justice. However, in spite of their importance, affirmative actions are frequently questioned by certain social groups, especially socially privileged groups, who argue that such policies are not meritocratic, constituting stereotypes aimed at quota and non-quota students. Thus, this article analyzes the possible stereotypes directed to quota students attending the course of administration of a Brazilian federal university. For this, a qualitative research was carried out with the accomplishment of 38 semi-structured interviews with quota and non-quota management students and documentary analysis. It is observed in the students' discourse the construction of the myth of the intellectual and academic inferiority of quota students, constituting social stereotypes that base the construction of an essential identity on who the quota holders are. However, there are spaces for resistance and the documentary analysis of students' performance, as well as their discourses, deconstruct the myth of shareholder inferiority and the stereotypes attributed to them. Therefore, in order to avoid the construction of stereotypes it is argued that affirmative actions should be conceived within nonessential identity logic.